Pengaruh Profitabilitas, Likuiditas dan Struktur Aktiva Terhadap Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015-2017 - Oki Oktaviana; Jawida NR Tampubolon; Nina Purnasari; Jihan Safitri; Nario Afandi PW Manao (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
It is an enterprise that seeks to convert or distribute raw materials, into half-finished products and into marketable products, and has the sale value of company management capabilities to increase corporate operations that is vital to the increase in corporate profits. The study aims to discover and understand the impact of profitability (ROA), liquidity (CR), and the structure of capital on manufacturing companies registered in the Indonesian stock exchange the 2015-2017 period. Research samples number 70 of the manufacturing companies, determined by sampling methods. The type of data used is the secondary data of a company's finance report 2015-2017. In research, this analysis technique used by means of linear regression analysis using tests and testing based on results suggests that profitability has little effect and no significance to the structure of capital, liquidity has a negative and significant impact on capital structure, and activation structures have no effect and no significance to the structure of capital. Based on the results of this study, it simultaneously proves that independent variables of profitability, liquidity and structure of assets do not affect the dependent variables of capital structures. Keywords : profitability, liquidity, activation structure and capital structure